2021
DOI: 10.2174/1573405616666201012154548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Small-animal Nano Scan PET/CT System using 89Zr

Abstract: Introduction: The purpose of the present work was to evaluate the imaging characteristics of 89Zr-PET in comparison with those obtained using fluorine-18 Fluorodeoxyglucose (18F-FDG) PET (a gold standard tracer in PET imaging) using a small-animal NanoScan PET/CT scanner. Methods: The system’s spatial resolution, sensitivity, uniformity, and image quality were measured on a Nano Scan small-animal PET/CT scanner according to the NEMA NU4-2008 protocols. For reconstruction images, we used 2D and 3D reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Taheri-Ledari R proposed a promising heterogeneous nanoscale catalytic system composed of chitosan, iron oxide nanoparticles, and copper oxide nanoparticles [13]. e aim of Alzimami K was to evaluate the imaging properties of standard tracers and to perform scanner comparisons with gold standard tracers in fluorodeoxyglucose imaging obtained using small animal standard tracers [14]. Although many people have been very rich in nano-CT research, few people realize that it is very meaningful to apply this technology to the exploration of tight oil.…”
Section: Introductionmentioning
confidence: 99%
“…Taheri-Ledari R proposed a promising heterogeneous nanoscale catalytic system composed of chitosan, iron oxide nanoparticles, and copper oxide nanoparticles [13]. e aim of Alzimami K was to evaluate the imaging properties of standard tracers and to perform scanner comparisons with gold standard tracers in fluorodeoxyglucose imaging obtained using small animal standard tracers [14]. Although many people have been very rich in nano-CT research, few people realize that it is very meaningful to apply this technology to the exploration of tight oil.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with earlier research applying PRC to PET image reconstruction, where the spatial resolution and boundary delineation would increase, while the noise in the image would also increase, especially at boundaries between low and high activity [ 12 , 18 ]. To the best of our knowledge, no research has demonstrated the effect of PRC for 82 Rb in in a NEMA NU-4 phantom, but it has been demonstrated for 89 zirconium [ 19 ], 124 iodine [ 13 ] and 68 gallium ( 68 Ga) [ 11 ]. These studies also found an increase in %SD and RC, with a decrease in SOR.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with earlier research applying PRC to PET image reconstruction, where the spatial resolution and boundary delineation would increase, while the noise in the image would also increase, especially at boundaries between low and high activity (12,18). To the best of our knowledge, no research has demonstrated the effect of PRC for 82 Rb in in a NEMA NU-4 phantom, but it has been demonstrated for 89 Zirconium (19), 124 Iodine(13) and 68 Gallium ( 68 Ga) (11). These studies also found an increase in %SD and RC, with a decrease in SOR.…”
Section: Nema Nu-4-inspired Phantommentioning
confidence: 93%